2013
DOI: 10.1016/j.jped.2012.10.001
|View full text |Cite
|
Sign up to set email alerts
|

A prospective study of risk factors for neurological complications in childhood bacterial meningitis

Abstract: Age < 12 months and severity of clinical presentation at admission were identified as the strongest predictors of neurological complications and may be of value in selecting patients for more intensive care and treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
27
2
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 27 publications
3
27
2
3
Order By: Relevance
“…(23) The significantly higher frequency of ME complications among children less than one year of age is consistent with that reported by Gomes et al, (24) who reported that complications were more predominant among Brazilian children aged less than one year of age (71%). On the other hand, the significantly higher frequency of ME complications among exclusively breastfed children in their first six months of life in the present study is in agreement with the finding reported among Sudanese children by Salih et al, (25) who found a relation between the lack of exclusive breastfeeding and high frequency of complications following bacterial ME.…”
Section: Discussionsupporting
confidence: 93%
“…(23) The significantly higher frequency of ME complications among children less than one year of age is consistent with that reported by Gomes et al, (24) who reported that complications were more predominant among Brazilian children aged less than one year of age (71%). On the other hand, the significantly higher frequency of ME complications among exclusively breastfed children in their first six months of life in the present study is in agreement with the finding reported among Sudanese children by Salih et al, (25) who found a relation between the lack of exclusive breastfeeding and high frequency of complications following bacterial ME.…”
Section: Discussionsupporting
confidence: 93%
“…If all of these died, the mortality would have actually been 35.9%. Our death rate is higher compared to studies conducted in children from wealthier countries like Kosovo, 2.6% (age one month–16 years) [ 17 ], Iceland, 4.4% (age ≤18.5y) [ 18 ], South Korea, 9.5% (age ≤18y) [ 19 ], and Iran, 10% (5m–10y) [ 20 ]. One comparable study from India reported a 16% death rate in children aged one month–five years [ 21 ].…”
Section: Discussionmentioning
confidence: 55%
“…Pediatricians should pay close attention to the children with positive bacterial cultures, because they are more likely to develop hydrocephalus. According to Namani et al, 28 children with bacterial meningitis previously treated with antibiotics do not show an increased incidence of neurologic complications. Initial treatment with 2 antibiotics is considered a risk factor for acute neurologic complications, but adjunctive dexamethasone therapy does not reduce the incidence.…”
Section: Discussionmentioning
confidence: 98%